(untitled) (Research, Society and Development, 2022)
Detritivorous arthropods are essential because they participate in recycling organic matter, decomposing pesticides, improving soil properties, conserving water, and reducing problems with plant diseases. Practices such as no-till and straw on soils can affect soil properties and populations of detritivorous arthropods. Brazil is the largest producer and consumer of common beans (Phaseolus vulgaris). Thus, this work aimed to determine the impact of no-till and straw planting on detritivorous arthropods on the "surface over ground" in common bean crops. In this way, common beans were cultivated in tillage and no-till with and without straw on the soil. During cultivation, the density of detritivorous arthropods on the soil was monitored using a pitfall trap. Sixteen morphospecies of detritivorous arthropods were observed on the surface of the ground. No-tillage and straw did not affect the number of detritivorous arthropod species. The most abundant morphospecies was the Collembola Entomobryidae and Hypogastrura sp. and the Coleoptera Scarabaeidae and Colopterus spp. No-till and straw positively affected the abundance of detritivorous arthropods. Therefore, no-tillage and straw in bean crops provide conditions for increasing detritivorous arthropod populations, improving soil properties.